1998
DOI: 10.1086/514934
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Oral Ciprofloxacin vs. Clarithromycin for Treatment of Acute Bacterial Exacerbations of Chronic Bronchitis

Abstract: In this prospective, multicenter, double-blind study, the efficacy of ciprofloxacin was compared with that of clarithromycin as therapy for patients with acute bacterial exacerbations of chronic bronchitis (ABECB) from whom a pretherapy pathogen was isolated; the efficacy was measured by the infection-free interval. Clinical and microbiological responses at the end of therapy were secondary efficacy variables. Patients randomly received either ciprofloxacin or clarithromycin (500 mg twice a day for 14 days). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
1
5

Year Published

2001
2001
2010
2010

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(61 citation statements)
references
References 27 publications
3
52
1
5
Order By: Relevance
“…In agreement with the studies of CHODOSH and coworkers [15,23], all clinical failures during the study therapy were counted as zero EFI days. For patients with no new exacerbation during the 1-yr observation period, the EFI was considered to be the number of days that had elapsed between the index exacerbation and the time point of the last information available (censored data).…”
Section: Follow-up and Exacerbation-free Interval Assessmentmentioning
confidence: 64%
“…In agreement with the studies of CHODOSH and coworkers [15,23], all clinical failures during the study therapy were counted as zero EFI days. For patients with no new exacerbation during the 1-yr observation period, the EFI was considered to be the number of days that had elapsed between the index exacerbation and the time point of the last information available (censored data).…”
Section: Follow-up and Exacerbation-free Interval Assessmentmentioning
confidence: 64%
“…It is reasonable to assume that a different approach, such as effective antibiotic treatment, may further reduce the rate of recurrence. Some evidence supports this hypothesis: 1) persistence of bacteria after antibiotic treatment for an exacerbation is associated with persistent bronchial inflammation [10]; 2) presence of bacteria in the airway (bronchial colonisation) is associated with more frequent and severe exacerbations [11]; 3) in a previous study, the presence of a persistent pathogen at the end of antibiotic therapy was significantly associated with a shorter infection-free period (pv0.01) [12]; and 4) another study showed superior bacterial eradication of moxifloxacin compared with standard therapy and this was followed by a prolonged infection-free interval that was significant for the first 5 months of follow-up [13]. Considering this evidence together, it can be hypothesised that effective antibiotic treatment that results in bacterial eradication may prevent recurrence, at least during the first months after the exacerbation, which is in agreement with the "fall and rise" hypothesis of bronchial bacterial infection [14].…”
Section: Miravitlles a Torresmentioning
confidence: 88%
“…This is particularly important, because most studies of antibiotics in exacerbations of chronic bronchitis have been modelled on pneumonia studies. No doubt, this study [6], together with the previous quinolone studies [13,16] and the lessons learned from the past [12,17,18], will guide the design of the new generation of clinical trials of antibiotics in exacerbations of chronic obstructive pulmonary disease [20].…”
Section: Miravitlles a Torresmentioning
confidence: 99%
“…In clinical trials with antibiotics in exacerbations of COPD, a prolonged time to the next exacerbation has been observed in patients who eradicate the bronchial pathogen after an exacerbation [18,19]. This suggests that in patients who effectively eradicate bacteria more time is needed to achieve the threshold of bacterial counts required for an exacerbation to occur, compared with patients who cure the exacerbation but in whom bacteria still persist after antibiotic treatment [20,21].…”
Section: Pharmacological Prevention Of Exacerbations Antimicrobialsmentioning
confidence: 99%
“…Instead, the rationale for the use of the fluoroquinolone moxifloxacin for the treatment of stable COPD is based on its antibacterial efficacy. Bacterial eradication reduces the inflammatory burden of the airways [29] and may eventually prevent the development of exacerbations [18,20,30]. Treatment with moxifloxacin has been efficacious in eradicating bacteria from the airways but new strains of colonising bacteria were present again after 8 weeks of antibiotic treatment, indicating that recolonisation is extremely frequent in a subset of patients with COPD [31].…”
Section: Review: Prevention Of Copd Exacerbationsmentioning
confidence: 99%